Global Principles of Sustainable Tourism Development Ecological, Economic and Cultural - I Nyoman Nurjaya (Fakultas Hukum, Universitas Warmadewa, 2022)
Indonesia is known as a country that has the beauty of the natural panorama of the sea and land and also invaluable cultural resources for the development of national tourism, in order to realizing the welfare and prosperity of the people as mandated by the1945 Constitution of the Republic of Indonesia. This research focus on discuss Global Principles of Sustainable Tourism Development and Sustainable Tourism Development Policy in Bali Province and to analyze the management of tourism destination in KSPN Kintamani-Lake Batur. This research is a normative legal research. The data used are primary and secondary data. The result explaine that the main economic sector in Bali, on the one hand, tourism performance is required to reduce the negative impact of tourism development. Nationally, with the enactment of Law Number 10 of 2009 concerning Tourism and Government Regulation Number 50 of 2011 concerning the National Tourism Development Master Plan (RIPKN), the Bali Provincial Government is required to prepare a Regional Tourism Development Master Plan (RIPKD) as stated in Bali Provincial Regulation No. 10 of 2015 concerning the Bali Provincial Tourism Development Master Plan for 2015-2029, which contains visions, directions, and plans that direct the development of tourist areas in Bali.